Answer:
Please check the explanation.
Step-by-step explanation:
Given the inequality
-2x < 10
-6 < -2x
<u>Part a) Is x = 0 a solution to both inequalities</u>
FOR -2x < 10
substituting x = 0 in -2x < 10
-2x < 10
-3(0) < 10
0 < 10
TRUE!
Thus, x = 0 satisfies the inequality -2x < 10.
∴ x = 0 is the solution to the inequality -2x < 10.
FOR -6 < -2x
substituting x = 0 in -6 < -2x
-6 < -2x
-6 < -2(0)
-6 < 0
TRUE!
Thus, x = 0 satisfies the inequality -6 < -2x
∴ x = 0 is the solution to the inequality -6 < -2x
Conclusion:
x = 0 is a solution to both inequalites.
<u>Part b) Is x = 4 a solution to both inequalities</u>
FOR -2x < 10
substituting x = 4 in -2x < 10
-2x < 10
-3(4) < 10
-12 < 10
TRUE!
Thus, x = 4 satisfies the inequality -2x < 10.
∴ x = 4 is the solution to the inequality -2x < 10.
FOR -6 < -2x
substituting x = 4 in -6 < -2x
-6 < -2x
-6 < -2(4)
-6 < -8
FALSE!
Thus, x = 4 does not satisfiy the inequality -6 < -2x
∴ x = 4 is the NOT a solution to the inequality -6 < -2x.
Conclusion:
x = 4 is NOT a solution to both inequalites.
Part c) Find another value of x that is a solution to both inequalities.
<u>solving -2x < 10</u>
![-2x\:](https://tex.z-dn.net/?f=-2x%5C%3A%3C%5C%3A10)
Multiply both sides by -1 (reverses the inequality)
![\left(-2x\right)\left(-1\right)>10\left(-1\right)](https://tex.z-dn.net/?f=%5Cleft%28-2x%5Cright%29%5Cleft%28-1%5Cright%29%3E10%5Cleft%28-1%5Cright%29)
Simplify
![2x>-10](https://tex.z-dn.net/?f=2x%3E-10)
Divide both sides by 2
![\frac{2x}{2}>\frac{-10}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%3E%5Cfrac%7B-10%7D%7B2%7D)
![x>-5](https://tex.z-dn.net/?f=x%3E-5)
![-2x-5\:\\ \:\mathrm{Interval\:Notation:}&\:\left(-5,\:\infty \:\right)\end{bmatrix}](https://tex.z-dn.net/?f=-2x%3C10%5Cquad%20%3A%5Cquad%20%5Cbegin%7Bbmatrix%7D%5Cmathrm%7BSolution%3A%7D%5C%3A%26%5C%3Ax%3E-5%5C%3A%5C%5C%20%5C%3A%5Cmathrm%7BInterval%5C%3ANotation%3A%7D%26%5C%3A%5Cleft%28-5%2C%5C%3A%5Cinfty%20%5C%3A%5Cright%29%5Cend%7Bbmatrix%7D)
<u>solving -6 < -2x</u>
-6 < -2x
switch sides
![-2x>-6](https://tex.z-dn.net/?f=-2x%3E-6)
Multiply both sides by -1 (reverses the inequality)
![\left(-2x\right)\left(-1\right)](https://tex.z-dn.net/?f=%5Cleft%28-2x%5Cright%29%5Cleft%28-1%5Cright%29%3C%5Cleft%28-6%5Cright%29%5Cleft%28-1%5Cright%29)
Simplify
![2x](https://tex.z-dn.net/?f=2x%3C6)
Divide both sides by 2
![\frac{2x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%3C%5Cfrac%7B6%7D%7B2%7D)
![x](https://tex.z-dn.net/?f=x%3C3)
![-6](https://tex.z-dn.net/?f=-6%3C-2x%5Cquad%20%3A%5Cquad%20%5Cbegin%7Bbmatrix%7D%5Cmathrm%7BSolution%3A%7D%5C%3A%26%5C%3Ax%3C3%5C%3A%5C%5C%20%5C%3A%5Cmathrm%7BInterval%5C%3ANotation%3A%7D%26%5C%3A%5Cleft%28-%5Cinfty%20%5C%3A%2C%5C%3A3%5Cright%29%5Cend%7Bbmatrix%7D)
Thus, the two intervals:
![\left(-\infty \:,\:3\right)](https://tex.z-dn.net/?f=%5Cleft%28-%5Cinfty%20%5C%3A%2C%5C%3A3%5Cright%29)
![\left(-5,\:\infty \:\right)](https://tex.z-dn.net/?f=%5Cleft%28-5%2C%5C%3A%5Cinfty%20%5C%3A%5Cright%29)
The intersection of these two intervals would be the solution to both inequalities.
and ![\left(-5,\:\infty \:\right)](https://tex.z-dn.net/?f=%5Cleft%28-5%2C%5C%3A%5Cinfty%20%5C%3A%5Cright%29)
As x = 1 is included in both intervals.
so x = 1 would be another solution common to both inequalities.
<h3>SUBSTITUTING x = 1</h3>
FOR -2x < 10
substituting x = 1 in -2x < 10
-2x < 10
-3(1) < 10
-3 < 10
TRUE!
Thus, x = 1 satisfies the inequality -2x < 10.
∴ x = 1 is the solution to the inequality -2x < 10.
FOR -6 < -2x
substituting x = 1 in -6 < -2x
-6 < -2x
-6 < -2(1)
-6 < -2
TRUE!
Thus, x = 1 satisfies the inequality -6 < -2x
∴ x = 1 is the solution to the inequality -6 < -2x.
Conclusion:
x = 1 is a solution common to both inequalites.